ANALISIS EKSPOR INDONESIA TAHUN 1990-2019 - Tyas, Hania Puspitaning (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2022)
Export is an example of international trade activity. The growth of a country can be influenced by the rise and fall of the value of exports. In the long term, export activities will foster domestic industry which in time will increase economic growth through additional foreign exchange as a result of export activities. This study analyzes the influence of Foreign Direct Investment (FDI), Inflation, and the Official Exchange Rate on the value of exports in Indonesia during the period 1990-2019. This study uses time series data from 1990-2019. The method used is the Error Correction Model (ECM) which aims to determine the existence of long-term and short-term relationships that occur in each variable. The results show that FDI has an effect and is significant on the value of exports in the long run. Meanwhile, Inflation and the Official Exchange Rate have a significant and significant effect on the value of exports, both in the short and long term.